Biogas production from POME by using low intensity sonic wave: article - Raja Anzac, Raja Nor Syuhada; Ku Hamid, Ku Halim (2019)
Ultrasonic wave is the new technology that had been used as a pre-treatment to POME to enhance the solubility of organic matter by breaking down the large molecule in order to ease the anaerobic digestion by bacteria to produce high biogas yield. During the sonication of POME, there was release of gas happen because of the cavitation that created gas and vapor bubbles. The type of gas produce was been identified in order to know the value of the gas in terms of biofuel potential gas from the sonication process. Four samples of POME were conducted in the experiment and categorize as treated and the untreated POME. The treated POME undergoes sonication while the untreated POME act as a reference sample. The gas release from sonication of POME was examine to identify any presence of useful biogas that can be used as biofuel such as methane gas without need to go through anaerobic digestion. Based on the result obtained, the gas yield mostly consist of bioalcohol and some long chain alkanes based compound that were still acceptable to be used as biofuel. It was discovered that POME with sonication treatment produce higher amount of biofuel potential gas compared to the unsonicated POME.